Field evaluation of cowpea (Vigna unguiculata) varieties for grain and fodder production and for multiple disease resistance in Nigeria - ADEBITAN, S A; OLUFAJO, O O (The Indian Journal of Agricultural Sciences, 2013)
A field study was conducted during 1992-94 in rainy season (July-October) to evaluate 12 cowpea [Vigna unguiculata(L.) Wa1p.] varieties for grain and fodder production, and their resistance to the major prevalent diseases at Bauchi inNigeria. Cowpea varieties 'IAR 4/48-15-1', 'IT 89 KD-288','IT 89KD-275'.'IAR 7/180-4-5', 'IAR 2/180-4-9', and'IAR 2/180-4-12' significantly gave higher seed yields than others. Highest fodder (dry and fresh) yields were obtainedin 6 varieties, and high seed as well as fodder yields in 'IAR 2/180-4-12','IAR 7/180-4-5'.'IAR 2/180-4-9' and 'IT 89KD-288'. Only 'IAR 7/180-4-5' showed multiple disease resistance to scab (Elsinoe phaseoli Jenkins), anthracnose[Colletotrichum lindemuthianum (Sacc and Magnus) Lams scrib.] and bacterial blight [Xanthomonas campestris pvphaseoli (Smith) Dye].